Convalescent Plasma: The Relay Baton in the Race for Coronavirus Disease 2019 Treatment - Ouyang, Jing; Isnard, Stéphane; Lin, John; Fombuena, Brandon; Peng, Xiaorong; Routy, Jean-Pierre; Chen, Yaokai (Frontiers in Immunology, 2020)
Coronavirus disease 2019 (COVID-19) is a pandemic caused by the severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2). Most infected people have mild or moderate symptoms and recover without the need for extensive treatment. However, for serious ill patients, no specific treatments are currently available. Convalescent plasma therapy (CPT), a passive immunotherapy, involves infusing plasma from recovered people into actively infected people, and is thought to be a specific intervention to improve outcome in patients with severe COVID-19. The presumed mechanism involves neutralizing antibodies and antibody dependent cytotoxicity/phagocytosis. Previous CPT trials showed an effect in SARS and pilot studies suggest CPT is an effective and safe strategy for seriously ill COVID-19 patients. CPT is currently being tested in large randomized clinical trials. Herein, we critically review the mechanism, applications and the challenges for CPT in the treatment of severe COVID-19, paving the way toward vaccine and immunotherapy development.